HbA1c As Diabetes Mellitus Biomarker and Its Methods Evolution - Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
This literature aims to review various aspects of HbA1c as a Diabetes Mellitus (DM) biomarker and various HbA1c examination methods and their respective advantages and limitations. Diabetes mellitus is a condition characterized by chronic hyperglycemia and can lead to microvascular and macrovascular complications in the future. HbA1c has been used extensively over the last few decades to monitor glycemic control and assess microvascular and macrovascular risk. It has also been used as one of the diagnostic criteria for DM. HbA1c is hemoglobin A, which is glycated at the N terminal of its valine beta-globin chain and provides an overview of glycemic control over the past three months. HbA1c is often reported using % or mmol/mol units and can be adjusted to assess the average blood glucose level over the past three months. Various methods developed for HbA1c examination include immunoassay, boronate affinity, enzymatic, capillary electrophoresis, and Ion-Exchange High-Performance Liquid Chromatography (IE-HPLC), and each has its advantages and limitations. In addition to their advantages in detecting HbA1c, the capillary electrophoresis and IE-HPLC methods can also detect other types of hemoglobin and the presence of hemoglobin variants.